2019
DOI: 10.1177/1724600819847999
|View full text |Cite
|
Sign up to set email alerts
|

Predictive significance of CYFRA21-1, squamous cell carcinoma antigen and carcinoembryonic antigen for lymph node metastasis in patients with esophageal squamous cancer

Abstract: From January 2018 to May 2018, 108 patients with thoracic esophageal cancer underwent esophagectomy with two- to three-field lymph node dissection. Serum cytokeratin 19 fragment antigen 21-1 (CYFRA21-1), squamous cell carcinoma antigen, and carcinoembryonic antigen levels were detected before surgery. Preoperative serum levels of CYFRA21-1 and squamous cell carcinoma antigen were correlated closely with pN stage ( P = 0.000 and P = 0.045). CYFRA21-1 and pathological T status were independent predictors of lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…High expression of Cyfra21-1 is an important factor affecting the survival of patients with advanced NSCLC (21). The preoperative serum Cyfra21-1 level was an independent predictor of lymph node metastasis in patients with esophageal squamous cancer (13). Rapid and quantitative detection of urinary Cyfra21-1 is a non-invasive approach for the diagnosis and prognosis of bladder cancer (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High expression of Cyfra21-1 is an important factor affecting the survival of patients with advanced NSCLC (21). The preoperative serum Cyfra21-1 level was an independent predictor of lymph node metastasis in patients with esophageal squamous cancer (13). Rapid and quantitative detection of urinary Cyfra21-1 is a non-invasive approach for the diagnosis and prognosis of bladder cancer (14).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been proven that Cyfra21-1 can independently be used as a prognostic indicator of a variety of malignant tumors. Numerous studies have shown that it has important prognostic significance for middle and advanced cancers, such as esophageal cancer, bladder cancer, epithelial ovarian cancer, and intrahepatic cholangiocarcinoma (13)(14)(15)(16). Lei et al found that Cyfra21-1 could be used to predict the early recurrence of OPSCC by comparing between groups, and the concentration of Cyfra21-1 was related to the clinicopathological stage of OPSCC.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the early diagnosis and prolong the survival time for cancer patients, it is necessary to explore various sensitive tumor markers in cancers. Serum squamous cell carcinoma antigen (SCCA) is a commonly used clinical tumor marker for SCC, such as cervical SCC, head and neck SCC and ESCC [5][6][7]. To date, however, the prognostic role of SCCA in patients with ESCC remains controversial [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…CEA, cytokeratin 19 fragment 21‐1 (CYFRA21‐1), and squamous cell carcinoma antigen (SCC) were also evaluated for the diagnosis of ESCC. However, the sensitivity and specificity of these biomarkers are very limited in ESCC 8,9 …”
Section: Introductionmentioning
confidence: 99%
“…However, the sensitivity and specificity of these biomarkers are very limited in ESCC. 8,9 In the present study, we first used a ProcartaPlex Array to screen for serum proteins increased in 40 ESCC patients compared with the normal controls. By further verification of candidate serum markers with a larger sample of sera (174 ESCC patients and 189 normal controls), we found that serum eotaxin and IP-10 might be potential biomarkers in the diagnosis and therapeutic monitoring of ESCC patients.…”
Section: Introductionmentioning
confidence: 99%